Transitioning towards environmentally benign marine antifouling coatings - Carrier, Andrew J.; Carve, Megan; Shimeta, Jeff; Walker, Tony R.; Zhang, Xu; Oakes, Ken D.; Jha, Kshitij C.; Charlton, Tim; Stenzel, Martina H. (Frontiers in Marine Science, 2023)
Marine biofouling has been an issue since antiquity whose solutions have a history of negative environmental impact. The development of environmentally sustainable solutions is paramount as society is becoming more conscious of anthropogenic impacts on the global ecosystem, particularly the global oceans. Herein we include a brief overview of common strategies in the development of sustainable marine antifouling coatings in terms of their efficacy, durability, and environmental impact. We discuss technical challenges to the development of sustainable antifouling coatings; barriers and incentives to their market uptake; and advocate the necessity of multi-stakeholder collaboration, including scientists, engineers, industry groups, and regulators, toward the development of marketable and sustainable antifouling coating solutions.